Jack's garden - Cole, Henry (New York : Mulberry Books, 1997)
Cumulative text and illustrations depict what happens in Jack's garden after he plants his seeds.
School Library Journal
Five Owls
Child Study Children's Book Committee
4.5
K-3
Keywords: Gardening -- Fiction; Gardening -- Fiction